NEW DATA ON WATER ENVIRONMENT AND ORGANISM IN SUBMERGED CAVES AND SALTWATER LAKES IN HA LONG AND CAT BA AREAS - Ngai, Nguyen Dang; Thao, Dau Van; Thung, Do Cong; Thuy, Le Thi; Luong, Pham Van; Trang, Cao Thu; Luu, Vu Thi; Tien, Dam Duc; Quan, Nguyen Van; Chien, Pham Van (Vietnam Journal of Marine Science and Technology, 2016)
Submerged caves and saltwater lakes are 2 common habitat types in Ha Long and Cat Ba. However, depending on many different reasons so far they have been poorly studied both on environmental and biological characteristics. The initial results on environment and biological communities in 3 submerged caves (Hang Sang, Hang Toi, Qua Bang) and 3 saltwater lakes (Ang Dau Be, Ang Du, Ang Qua Bang) showed that: status of water environment was different among lakes, especially in the closed lake as Ang Du where salinity was low (9‰), while salinity in the lakes connected to the sea was equal to marine environment (23 - 27‰). Concentration of dissolved oxygen (DO) in saltwater lakes was high from 7.63 - 9.03 mg/L and higher than that in submerged caves and surrounding marine environment. Physical and chemical factors of water in the submerged caves were equivalent to the marine environment because these caves are connected to the sea and water regularly goes in and out according to tidal fluctuation. Organism communities in the submerged caves were abundant with over 142 species being found. The popular groups, sponge and soft coral, were distributed along the length of the caves. Several species with high economic value were commonly observed in the caves, including stone crab Myomenippe hardwickii, flower crab Portunus pelagicus, cone snails Trochus pyramis, shoemaker spinefoot Siganus sutor, snapper Lutjanus russelii ... Species that permanently live in cave were not detected. In the lakes where water is well exchanged to the sea, coral reefs were found and they formed a narrow reef around the lake. Sandy bars often appeared around the lake at the depth of 0.5 - 2 m, containing specialty species as phi (Sanguinolaria diphos), snout otter clam (Lutraria rhynchaena), sea cucumbers with high density (Ang Dau Be, Ang Qua Bang). There was no coral reef in the closed lake (Ang Du) because of low salinity. In this lake, stratification of temperature and salinity led to temperature on surface lower than that on bottom from 30C to 60C, this phenomenon is unusual.